Den russiske togmyten En kulturfilologisk tilnærming til russiskspråklig jernbanefiksjon - Lotsberg Bryn, Brita (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"How are languages and cultures affected not only by the landscapes we live in, but also by the ways in which we make our way through them? Can railway fiction contribute to illuminating questions related to a nation's history and identity? And what makes the stories about Russian, Soviet and post-Soviet trains different from railway literature with origins in other railway nations? Outside the country's borders Russian and Soviet trains are likely to be associated with exotic journeys, particularly by the Trans-Siberian railway. This book explores other aspects of this vast empire's railways. Through philological and cultural analyses, primarily of literary fiction, but also of popular cultural and documentary texts, the author demonstrates how and why the railway gradually became part of the Russian and Soviet peoples' culture and national consciousness. She describes how metaphors and aphorisms related to trains were applied in propaganda, and subsequently became subject to linguistic play and literary deconstruction. And last, but not least this monograph shows how the railway forms a dark backdrop for literary representations of deportations, forced labour and prison camps. The book addresses specialists and students of Russian, as well as readers with a general interest in Russia, languages, literature and cultural theory."